Pendidikan Akhlak Imam Al-Ghazali Dan Syaikh Abdul Qadir Al-Jailani (Studi Komparatif Kitab Bidayatu Al-Hidayah dan Kitab Nashoihu Al-Jailani) - Mustofa Mustofa; Lailatul Rif'ah (FIRDAUS, 2025)
Moral education is a fundamental aspect in the formation of human character that cannot be separated from the overall educational process. This study aims to comparatively examine the concept of moral education according to Imam Al-Ghazali in the Book of Bidayatu Al-Hidayah and Shaykh Abdul Qadir Al-Jailani in the Book of Nashoihu Al-Jailani. The approach used is qualitative with the type of library research and comparative descriptive analysis method. The results of the study show: (1) Imam Al-Ghazali emphasizes moral education that includes relationships with Allah, oneself, teachers, parents, friends, and others in detail and in a communicative-democratic manner; (2) Shaykh Abdul Qadir Al-Jailani places more emphasis on self-purification, piety, introspection, and a global religious attitude; (3) Both have similarities in discussing noble morals, the importance of honesty, guarding the tongue, sincerity in deeds, and the goal of seeking Allah's pleasure; (4) The values ​​of moral education of both figures are in line with the character education curriculum in Indonesia.